Frequency of patent foramen ovale in migraine patient with aura versus migraine patient without aura in outpatient department of tertiary care hospital - Gul, Amber; Hashmat, Asif; Khan, Umer Farooq; Gul, Warda (International Journal of Pathology, 2026)
Background: Migraine is a highly prevalent neurological disorder and a leading cause of disability worldwide. Patent foramen ovale (PFO) has been implicated in the pathogenesis of migraine, particularly migraine with aura; however, evidence from Pakistan remains scarce. This study aimed to compare the frequency of PFO between patients with migraine with aura (MA) and those with migraine without aura (MOA) attending a tertiary care hospital. Methods: This comparative cross-sectional study was conducted at the Department of Neurology, Pak Emirates Military Hospital (PEMH) Rawalpindi, from Jan/2025 to June/2025, including 68 patients, classified into two groups according to migraine type: Group A (MA, n=36) and Group B (MOA, n=36). All participants underwent contrast-enhanced transthoracic echocardiography for assessment of PFO. Data was analyzed through SPSS-24. Chi-square / Fisher’s Exact test was used, keeping p value<0.05 as significant. Results: Mean age and headache duration were comparable between groups. The prevalence of PFO was significantly higher in the MA group than in the MOA group (41.7% vs. 11.1%; p=0.003). The distribution of PFO categories also differed significantly between the groups (p=0.013). No significant differences were observed between the groups regarding age distribution, gender, family history of migraine, or headache severity (all p>0.05). Additionally, PFO status was not significantly associated with age, gender, or headache severity. Conclusion: Patients who had migraine with aura had significantly higher frequency of PFO compared to those without aura.